ERIC.
ERIC (Education Resource Information Center) is een gezaghebbende databank met indexering en full-text van onderwijsgerelateerde literatuur en andere bronnen. // ERIC provides ready access to education literature to augment American education by increasing and facilitating the use of educational research and information to improve practice in learning, teaching, educational decision-making, and research. ERIC provides coverage of journal articles, conferences, meetings, government documents, theses, dissertations, reports, audiovisual media, bibliographies, directories, books and monographs.
Keywords: Bibliografieën; Lerarenopleiding; Onderwijskunde; Tijdschriftartikels